Printed Elliptically Polarized Star Dipole Antenna - Ab Mutalib, Muhammad Haziq (Universiti Sains Malaysia, 2018)
The increases usage of mobile phone has led to a higher demand on capacity and bandwidth of a communication system. The latest development of mobile phones has required a huge amount of data transmission over communication system. By employing dual polarization multiple-in multiple-out (MIMO) method, it able to improve and offer high capacity and bandwidth to meet this huge demand. Crossed dipole antenna or known as STAR dipole antenna which can produce elliptical polarisation was formed where it is able to improve the orthogonality that required for MIMO multiplexing, thus it will improve the multiplexing gain over dual linear polarisation. In previous research, dual elliptically polarised antenna prototype was designed by using copper wire but the prototype is suitable for demonstration purpose as the design was too large and the results was unable to be the same as the first design because of the wire specification. This work therefore aims to design STAR dipole antenna with frequency 2.4GHz in CST software to form elliptical polarisation and print the antenna design onto substrate and make it planar structure as it easy to manufactured and more accurate. As the S-parameter, gain and radiation pattern was characterized, the results concluded that the original STAR dipole antenna had a slightly higher gain than the printed STAR dipole antenna but radiation pattern for both printed and original STAR dipole antenna still quite similar therefore it can be used as substitute to the original antenna.